Hubungan Gaya Kepemimpinan Dengan Kinerja Tenaga Kesehatan - Wasiyem, Wasiyem; Syafitri, Najla Rifda; Kudadiri, Nazli Ba’iah; Komaruddin, Niswah Zhafira; Manurung, Revina Aulia (Journal of Health Education Law Information and Humanities, 2025)
Leadership is a key aspect for managing the success of health services. A health service really requires maximum health personnel, therefore health organizations must have good work efficiency. Developing good work efficiency requires health workers who have good work skills, but developing good work results requires a strategy, and one example that can be implemented is by using leadership style methods. This research aims to convey where there is an important relationship between leadership style and the performance of health workers. The position of leader in an organization or agency plays an important role in success. The leader mentioned is an organizational leader who has a vision and mission that leads to the future and has characteristics that can be used as an example for the individuals he is leading. A leader must have an important role and be able to provide valuable support and be able to resolve challenges or problems that will occur. In this research, researchers used the Systematic Literature Review (SLR) method which focuses on examining all research. Information obtained from national journals using Google Scholar using the same keywords, namely "Leadership Style, Health Worker Performance, Relationships, Competence" using 15 articles starting from 2015-2024. So researchers can conclude that there is a relationship between leadership style and the performance of health workers.